2016
DOI: 10.1007/s11605-015-2960-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CDT1 Is a Predictor of Poor Survival in Patients with Hepatocellular Carcinoma

Abstract: Overexpression of CDT1 and MCM7 in hepatocellular carcinoma correlates with DNA damage response, and CDT1 overexpression is a significant prognostic biomarker in hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 34 publications
6
29
2
Order By: Relevance
“…Further studies are needed to fully elucidate the relationships between clinical behaviors and CDT1 or geminin expression. Although there were no apparent associations between γ‐H2A.X and prognostic factors, as described by Karavias et al, γ‐H2A.X expression tended to decrease in patients with advanced T and M stages in our study. These findings suggested that γ‐H2A.X may play a key role in OSCC progression.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Further studies are needed to fully elucidate the relationships between clinical behaviors and CDT1 or geminin expression. Although there were no apparent associations between γ‐H2A.X and prognostic factors, as described by Karavias et al, γ‐H2A.X expression tended to decrease in patients with advanced T and M stages in our study. These findings suggested that γ‐H2A.X may play a key role in OSCC progression.…”
Section: Discussioncontrasting
confidence: 52%
“…Additionally, slightly high CDT1 expression was correlated with OSCC recurrence and postoperative metastasis, although high CDT1 expression also tended to be associated with patient survival. In a previous study, overexpression of CDT1 was shown to be a predictor of poor survival in patients with hepatocellular carcinoma . Thus, the expression of CDT1 may depend on the tumor type and grade.…”
Section: Discussionmentioning
confidence: 88%
“…1,2 The pathogenesis of HCC is very complicated with lots of genes and proteins to participate in. [3][4][5] The advanced clinical stage system is the only accepted method for predicting the prognosis of clinical HCC patients with progressive disease, with surgery being the only major therapeutic option. Diagnosis of HCC is usually dependant on image techniques, blood indicators, and histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Cdc6 and Cdt1 has been shown to contribute to oncogenesis 6, 7 and their upregulations are linked to cancer progression in various types of cancer 813 . Cdc6 has been shown to be regulated by estrogen 14 , and is downregulated in methionine-mediated inhibition of cell proliferation 15 .…”
Section: Introductionmentioning
confidence: 99%